Recent Progress in 3D Printing of Bioinspired Structures - Wang, Danfeng; Chen, Dongdong; Chen, Zeyu (Frontiers in Materials, 2020)
Over millions of years of evolution, species in nature have gradually adopted bio-structures. These structures have specific mechanical, hydrodynamic, optical, and electrical properties, which provide humans with valuable abilities to design and fabricate high-performance components and devices. However, traditional fabrication technologies cannot accurately reproduce or imitate the complicated and exquisite bioinspired structures, which restrict the development and application of biomimetic study. Due to the emergence and development of 3D printing technologies, more bioinspired structures can now be designed and fabricated. Recent progress in the 3D printing of structures inspired by species in nature, such as springtails, filefish, abalone shell, conch shell, wheat awn, plant stem, and wood, are reviewed in this paper, which also discusses current challenges and potential future developments in 3D printing for bioinspired structures.